Determinants of long-term clinical outcomes in patients with angina but without obstructive coronary artery disease: a systematic review and meta-analysis. (23rd April 2018) - Radico, Francesco; Zimarino, Marco; Fulgenzi, Fabio; Ricci, Fabrizio; Di Nicola, Marta; Jespersen, Lasse; Chang, Su Min; Humphries, Karin H; Marzilli, Mario; De Caterina, Raffaele
Abstract: Aims: The long-term prognosis of angina in patients without obstructive coronary artery disease (CAD) is uncertain. To assess the incidence of long-term adverse outcomes in such patients. Methods and results: We searched PubMed, Cochrane Library, the Embase database, and the Clinical Trials Registry for studies published in English until January 2017, assessing the composite primary outcome of all-cause death and non-fatal myocardial infarction using random-effects models to estimate pooled incidences. We identified 54 studies, reporting outcomes in overall 35 039 patients (mean age 56, male/female ratio 0.51, 99 770 person-years) with angina and no obstructive CAD. After a median follow-up of 5 years (interquartile range 3–7 years), the pooled incidence of the primary outcome was 0.98/100 person-years [95% confidence interval (CI) 0.77–1.19%], with considerable heterogeneity among studies ( I 2 = 91%, P < 0.001). The primary outcome was associated with prevalent dyslipidaemia ( P = 0.016), diabetes ( P = 0.035), and hypertension ( P = 0.016). Studies enrolling patients with less-than-obstructive CAD showed a higher incidence of the primary outcome (1.32/100 person-years, 95% CI 1.02–1.62) compared with studies including only patients with 'entirely normal' coronary arteries (0.52/100 person-years, 95% CI 0.34–0.79, respectively; P < 0.01). The incidence of the primary outcome did not differ significantly between studies enrolling only patients with documented myocardial ischaemia and those studies enrolling patients regardless of presence of ischaemia. However, ischaemia documented by non-invasive imaging techniques was associated with a higher incidence of events ( P = 0.02). Overall, these patients, however, suffered from a high incidence of recurrent hospitalization. Conclusion: Angina without obstructive CAD has a heterogeneous prognosis. A main determinant of major adverse events is the presence of 'some' coronary atherosclerosis, with unequivocal myocardial ischaemia being associated with worse clinical outcomes. Patients' quality of life is also worsened by the high incidence of hospitalization, angina recurrence, and repeated coronary angiography.